Salidroside inhibited the proliferation of gastric cancer cells through up-regulating tumor suppressor miR-1343-3p and down-regulating MAP3K6/MMP24 signal molecules - Xiaoping Wang; Zhendong Zhang; Xiaolan Cao (Cancer Biology & Therapy)
Salidroside inhibited the proliferation of cancer cell. Nevertheless, the mechanism has not been completely clarified. The purpose of the study is to explore the mechanisms of salidroside against gastric cancer. To analyze the changes of microRNA (miRNA) in gastric cancer cells under the treatment of salidroside, the miRNA expression was analyzed by using RNA-seq in cancer cells for 24 h after salidroside treatment. The differentially expressed miRNAs were clustered and their target genes were analyzed. Selected miRNA and target mRNA genes were further verified by q-PCR. The expressions of target genes in cancer cells were detected by immunohistochemistry. Cancer cell apoptotic index was significantly increased after salidroside treatment. The proliferation of gastric cancer cells were blocked at S-phase cell cycle. The expression of 44 miRNAs changed differentially after salidroside treatment in cancer cells. Bioinformatic analysis showed that there were 1384 target mRNAs corresponding to the differentially expressed miRNAs. Surprisingly, salidroside significantly up-regulated the expression of tumor suppressor miR-1343-3p, and down-regulated the expression of MAP3K6, STAT3 and MMP24-related genes. Salidroside suppressed the growth of gastric cancer by inducing the cancer cell apoptosis, arresting the cancer cell cycle and down-regulating the related signal transduction pathways. miRNAs are expressed differentially in gastric cancer cells after salidroside treatment, playing important roles in regulating proliferation and metastasis. Salidroside may suppress the growth of gastric cancer by up-regulating the expression of the tumor suppressor miR-1343-3p and down-regulating the expression of MAP3K6 and MMP24 signal molecules.